2021
DOI: 10.1002/cne.25130
|View full text |Cite
|
Sign up to set email alerts
|

Macaque monkey trigeminal blink reflex circuits targeting orbicularis oculi motoneurons

Abstract: The trigeminal blink reflex plays an important role in protecting the corneal surface from damage and preserving visual function in an unpredictable environment. The closing phase of the human reflex, produced by activation of the orbicularis oculi (ObOc) muscles, consists of an initial, small, ipsilateral R 1 component, followed by a larger, bilateral R 2 component. We investigated the circuitry that underlies this reflex in macaque (Macaca fascicularis and Macaca mulatta) monkeys by the use of single and dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…So we do not believe that reticular projections are responsible for the labeled terminals observed in CC. This is a noteworthy finding, as the paratrigeminal reticular formation in the pons (Figure 14) has been implicated in activating both orbicularis oculi motoneurons and retractor bulbi motoneurons during trigeminally elicited blinks (cat: Holstege et al, 1986; Holstege & Tan, 1988; rabbit: van Ham & Yeo, 1996; macaque: May & Warren, 2021). It appears that the pontine portion of this paratrigeminal region is solely responsible for the excitatory components of the blink closing phase, and that the inhibitory circuits supplying III are instead located in the region lining the rostral edge of pV.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…So we do not believe that reticular projections are responsible for the labeled terminals observed in CC. This is a noteworthy finding, as the paratrigeminal reticular formation in the pons (Figure 14) has been implicated in activating both orbicularis oculi motoneurons and retractor bulbi motoneurons during trigeminally elicited blinks (cat: Holstege et al, 1986; Holstege & Tan, 1988; rabbit: van Ham & Yeo, 1996; macaque: May & Warren, 2021). It appears that the pontine portion of this paratrigeminal region is solely responsible for the excitatory components of the blink closing phase, and that the inhibitory circuits supplying III are instead located in the region lining the rostral edge of pV.…”
Section: Discussionmentioning
confidence: 90%
“…This downward motion is produced by relaxing the levators, which releases the tension in the check ligaments of the eyelids, pulling them downward (Evinger et al, 1991; Sibony et al, 1991). We previously showed that cells within pV and in the adjacent paratrigeminal reticular formation in the macaque do, in fact, provide a monosynaptic input to orbicularis oculi motoneurons in the contralateral facial nucleus (Figure 14, light and dark blue circuits, respectively) (May & Warren, 2021). So both the excitatory and inhibitory paths are bilateral and direct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 27 The sections from the WGA-HRP injection were reacted using tetramethylbenzidine with ammonium molybdate as a chromagen in 0.1 M, pH 6.0 PB, as previously described. 28 These sections were counterstained with cresyl violet. All sections were dehydrated in a graded series of ethanols, cleared in toluene, and coverslipped.…”
Section: Methodsmentioning
confidence: 99%